Magnesium intake is inversely associated with the risk of metabolic syndrome in the REasons for geographic and racial differences in stroke (REGARDS) cohort study. Issue 4 (April 2021) - Dibaba, Daniel T.; Chen, Cheng; Lu, Liping; Bidulescu, Aurelian; Fly, Alyce D.; Xun, Pengcheng; Judd, Suzanne E.; Cushman, Mary; Kahe, Ka
Summary: Objective: To investigate the longitudinal association between magnesium (Mg) intake and the risk of metabolic syndrome (MetS). Methods: Poisson regression models with robust standard error estimation were used to examine the association between total Mg intake and the risk of MetS in 6802 participants aged ≥45 years at baseline in the REasons for Geographic And Racial Differences in Stroke (REGARDS) study. Dietary data were collected using the modified Block 98 food frequency questionnaire (FFQ) at baseline and incident MetS was diagnosed during follow-up if a participant had three or more of the five components of MetS based on the harmonized definition. Results: A total of 1470 participants developed MetS during an average follow-up of 10 years. Comparing the highest quintile of total Mg intake (>437.9 mg/day) to the lowest group (<223.5 mg/day), total Mg intake had a significant inverse association with the risk of MetS [relative risk (RR) = 0.79 (0.63, 0.98), P trend  = 0.043]. Dietary Mg intake was inversely associated with MetS [RR = 0.72 (0.56, 0.91), P trend  = 0.006]. Adjusting for baseline components of MetS attenuated the associations, but the linear trends remained. Conclusion: The findings from this study indicate that dietary Mg intake was inversely associated with the risk of MetS. We recommend further studies to explain the underlying mechanisms of action.